Association of cardio-ankle vascular index with diastolic heart function in hypertensive patients. (July 2014) - Kim, Hyungseop; Kim, Hye-Soon; Yoon, Hyuck-Jun; Park, Hyoung-Seob; Cho, Yun-Kyeong; Nam, Chang-Wook; Hur, Seung-Ho; Kim, Yoon-Nyun; Kim, Kwon-Bae
Abstract Arterial stiffness is an important risk factor of impaired left ventricular (LV) diastolic function as well as systolic dysfunction. The cardio-ankle vascular index (CAVI) and the ambulatory arterial stiffness index (AASI) can evaluate arteriosclerosis. We analyzed the relationship between arterial stiffness and diastolic function, and then compared the two methodologies to assess which method could serve as a more informative tool for diastology. In total, 136 patients with hypertension underwent 24-h ambulatory blood pressure monitoring (ABPM) and echocardiography including ventricular arterial coupling (VAC). Arterial stiffness was estimated using both CAVI and AASI derived from ABPM. Patients were classified into LV diastolic dysfunction and normal function groups. Those with diastolic dysfunction had a higher CAVI and AASI. Aside from LV torsion, mitral inflow parameters, tissue Doppler velocities and VAC showed a significantly greater association with CAVI, relative to AASI. The receiver operating characteristic curve analysis revealed that CAVI [area under the curve (AUC) = 0.869, p < 0.001] provided significantly more favorable accuracy for diastolic dysfunction compared with AASI (AUC = 0.672, p = 0.004). Multiple logistic regression analyses showed that CAVI [Odds ratio (OR) = 5.1, p = 0.009] had a greater association with diastolic dysfunction, relative to age, systolic blood pressure or AASI (OR = 1.4, p = 0.043). This study indicates that CAVI clinically provides diastolic functional information much better in hypertensive patients than AASI.